Geometria Hiperbólica: uma proposta didática em ambiente informatizado - Cabariti, Eliane (2004)
The main aim of this work is to contribute to the process of teaching and learning of geometry, in particular the non-Euclidean geometries, seeking to support the implementation of proposals associated with the introduction of a hyperbolic model, with the help of a computational tool, in mathematics teacher education courses. To this end, we conducted an experimental study to investigate the possible relations that teacher educators of Euclidean geometry establish when asked to solve situations involving notions of hyperbolic geometry, using the software Cabri-géomètre. The activities developed for the experimental study were inspired by the principals for the development of thought-revealing tasks, described by Lesh et al. (2000). Our analyses were based on two aspects: the dynamics behind movements between the geometrical domains Euclidean geometry and hyperbolic geometry as well as interactions between the spatio-graphical and theoretical fields (Laborde, 1999) and the role of Cabri as a tool for construction, exploration and validation, especially with respect to its dynamic aspects and the different possible drag modes (Olivero, 2002). Through our analysis of teachers' interactions with these situations, we confirmed the importance of the use of the hyperbolic menu of Cabri, fundamental for access to representations of hyperbolic objects favouring the understanding of concepts, properties and relations involved in this domain. The results of this study enabled us to reconsider some choices, leading to the re-design of the activities included in our initial proposal, in particular with reference to the makeup and use of the tools available in Cabri-géomètre. As a consequence, we were able to present a new pedagogic proposal consistent with the original aims